PENERAPAN DIGITAL MARKETING SEBAGAI SOLUSI PEMASARAN EFEKTIF BAGI PELAKU USAHA KERIPIK SINGKONG KUBE MELATI DI DESA TEMBELING - Dwi Septi Haryani; Octojaya Abriyoso; Betty Leindarita; Imran Ilyas; Satrio Bimo Syahputro; Ulfa Oktavani Nasution (Bajang Institute, 2025)
In the development of the digital era, digital-based marketing has become a significant tool for small and medium enterprises (SMEs) to expand market reach and enhance competitiveness. This study focuses on the implementation of digital marketing strategies for cassava chips businesses managed by the Joint Business Group (KUBE) Melati in Tembeling Village. The community service activities carried out included training on the use of social media, e-commerce platforms, and the creation of digital promotional content. The methods applied consisted of observation, initial interviews, practical training, and the process of monitoring and evaluating implementation. The results of this program indicate an improvement in the understanding and skills of SMEs in utilizing digital media, such as creating business accounts on Instagram and Facebook, as well as optimizing Google Maps to facilitate consumer access. The implementation of digital marketing has proven effective in increasing product visibility and sales potential, contributing positively to the local economy. These findings highlight the importance of digital empowerment for SMEs as a key strategy to drive sustainable growth